Additive prognostic value of high baseline coronary flow velocity to ejection fraction during resting echocardiography: 3-year prospective study - Zagatina, Angela; Guseva, Olesya; Kalinina, Elena; Rigo, Fausto; Caprnda, Martin; Masan, Jan; Gazdikova, Katarina; Firment, Peter; Ullrich, David; Gaspar, Ludovit; Kruzliak, Peter; Shmatov, Dmitry (Acta cardiologica, 2023)
BACKGROUND: There is a lack of information about the prognostic value of high velocity in coronary arteries during echocardiography. The present study was aimed at investigating the three-year prognostic value of coronary velocity assessment in all patients who were referred for echocardiography examination. METHODS: The prospective study comprises 747 consecutive patients. Death, myocardial infarction (MI), acute coronary syndrome (ACS), and/or revascularisation were defined as major adverse cardiac events (MACE). Routine echocardiography was added with coronary velocity assessment in the left main, anterior descending, or circumflex coronary arteries by the Doppler method. RESULTS: During a median follow-up of 36 months, 192 patients experienced MACE. Deaths occurred more frequently in patients with high local velocity in proximal left-sided segments vs. in middle left-sided segments vs. patients without high coronary velocity (9 vs. 3 vs. 1%, p < 0.0001). Death/MI/ACS occurred in 17 vs. 7 vs. 1%, p < 0.0001, respectively. Age (HR 1.04, 95% CI 1.00; 1.06; p < 0.04), a velocity more than 65 cm/s in any proximal segments of the arteries (HR 4.7, 95% CI 1.9; 11.9; p < 0.002), ejection fraction (HR 0.97, 95% CI 0.94; 0.99; p < 0.007) were strong independent prognostic predictors of death/MI/ACS. The maximal velocity of coronary flow velocity had a significant additive prognostic value to ejection fraction. CONCLUSIONS: The coronary velocity parameters give long-term prognostic information that can be used to identify persons with a high risk of MACE in consecutive non-selected patients.
Keywords: Coronary Vessels; prospektivní studie; Coronary Circulation; infarkt myokardu; transthoracic echocardiography; Humans; lidé; Blood Flow Velocity; Myocardial Infarction; koronární cévy; Echocardiography; Stroke Volume; Prospective Studies; rychlost toku krve; prognóza; tepový objem; Prognosis; koronární cirkulace; cardiovascular prognosis; Coronary artery flow velocity; coronary Doppler; echokardiografie; coronary stenoses